Intelligent Automated System for knowledge control of students of higher education institutions (Journal of Information Technologies in Education (ITE), 2009)
Conception of construction of the intellectual automated systems of evaluation of knowledge’s. The offered system foresees the presence of such subsystems: functional subsystem of transformation of information from external representation in intersystem information; subsystems of transformation from intersystem presentation of information in external information; subsystems of representation of knowledge’s, which includes the block of forming of results and system of artificial intelligence.
Keywords: automated evaluation system; current control; final control; linguistic model; mathematical model; module control; piece intellect; system of evaluation of knowledges; testing